God Is Beautiful - Devin Stewart (International Institute of Islamic Thought, 2016)
God is Beautiful is the English translation of a work originally submitted as a doctoral dissertation in Islamic studies at the University of Bonn in 1997 and published as Gott ist Schön: Das ästhetische Erlebung des Koran in 1999. Four printings since then attest to its popularity, which stems from its handling of a fascinating topic – Muslims’ experience of the Qur’an. This subject has been largely ignored in western scholarship, notable exceptions being art historical investigations of Qur’anic calligraphy and Kristina Nelson’s work on Qur’anic recitation. Rather than attempting a historical, linguistic, or grammatical analysis of the Qur’an, Kermani here engages in reader-response criticism to explain how the Qur’an both affected and continues to affect Muslim readers. This work presents itself as an alternative path to the Orientalists’ negative assessments of the Qur’an as an aesthetic text, which implied that Muslims’ claims about its beauty were simply the results of bias, devotion, blind adherence to tradition, and imperfect understanding. Kermani divides the discussion into six chapters, each of which investigates the topic from a different angle. Chapter 1, “The First Listeners,” discusses accounts of early reception of the Qur’an, stressing that from the very beginning its appeal was its linguistic beauty as much as the content of its message. He examines, among many others, the famous example Umar ibn al-Khattab’s conversion after he heard the beginning of Sūrat Ṭāhā (Q. 20) and was enraptured by its beauty and eloquence. The aesthetic experience of the Islamic message was thus inseparable from its theological or religious aspects. Chapter 6, “The Sufi Listeners,” makes a similar point by focusing on the reception of the Quran in mystical circles and especially on accounts of qatlā al-Qur’ān, figures who, upon hearing certain verses, were so affected emotionally that they died on the spot. Through its linguistic form, the Qur’an has a visceral effect on the hearer that cannot be reduced to the mental reception of doctrine ...